(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Mycobacterium Tuberculosis (M. tuberculosis) is the bacterium causes the diseases called tuberculosis. It is one of the most serious global health issues across the world. M. tuberculosis’ molecular typing is applied in different types of epidemiological conditions. It is also used in different modes of clinical management. In modern medical science, M. tuberculosis is typed through different techniques. Selecting the best technique according to the existing laboratory conditions and location-specific geographical features are important for M. tuberculosis typing. Restriction Fragment Length Polymorphism (RFLP) examination is considered as the best standard for molecular epidemiologic examination of tuberculosis. This process of investigation is based on IS6110 standard. A few species of the Mycobacterium Tuberculosis Complex (MTBC), especially Mycobacterium tuberculosis that is responsible for tuberculosis disease in human (commonly called TB) are the first reason of death connected to a distinct pathogen globally. In the last fifteen years, medical studies have improved a lot that has helped to understand MTBC more closely and traced its long co-evolution with the human race. It is capable of remaining latent in the human body. Humans are in fact its extraordinary asymptomatic career. Almost, one-third of the entire human population is the latent career of this bacterium. It is found to be highly resistant to antibiotics that are a proof of its evolutionary success.